CONSTITUTIONAL PROTECTION OF FREEDOM OF EXPRESSION IN THE DIGITAL SPACE IN CRITICISM OF THE IMPLEMENTATION OF THE CORETAX SYSTEM - Purwanto; Hanuring Ayu; Ariy Khaerudin (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The implementation of the Coretax System as part of Indonesia's tax administration digital transformation has generated extensive public responses through digital platforms. Public criticism of this policy constitutes a form of participation protected as a constitutional right; however, its exercise often intersects with legal restrictions aimed at safeguarding public order and the rights of others. This study examines the constitutional status of freedom of expression in relation to public criticism of the Coretax System, the legal protection afforded to such expression, and the constitutional limitations governing its exercise in the digital sphere. This research employs a normative legal method using statutory, conceptual, and case approaches. Legal materials were analyzed qualitatively through the interpretation of the 1945 Constitution of the Republic of Indonesia, statutory regulations, Constitutional Court decisions, and international human rights instruments. The findings indicate that criticism of the implementation of the Coretax System constitutes constitutionally protected freedom of expression provided that it is exercised responsibly and does not infringe upon the rights of others. Restrictions on freedom of expression are constitutionally permissible only when prescribed by law, pursue legitimate objectives, and satisfy the principles of legality, necessity, and proportionality as reflected in Article 28J of the 1945 Constitution, Article 19 of the International Covenant on Civil and Political Rights (ICCPR), Constitutional Court Decision Number 50/PUU-VI/2008, and Constitutional Court Decision Number 115/PUU-XXII/2024. This study proposes constitutional parameters for distinguishing protected public criticism from expressions that may legitimately be restricted within a democratic rule of law.